APLIKASI PATI ASETAT SEBAGAI CARRIER AGENT ANTOSIANIN DARI UBI JALAR UNGU - Hendy Suryandani, Indah Yuliasih, dan Titi Candra Sunarti (Jurnal Teknologi Industri Pertanian, 2019)
Purple sweet potato (Ipomoea batatas L. Poir) anthocyanins is a source of natural colorant which has functional characteristic such as antioxidant, antibacterial, antimutagenic and anticarcinogen functions. The weaknesses of purple sweet potato anthocyanins are easily to degradation by pH, temperature, and light, but it can be improved by adding carrier agent. Acetilated starch is one of modified starch that has potential to be a carrier agent because of its ability to minimize decreasing active compound. The methodologies of the research were preparation and characterization of raw material, determination of the ratio of slurry and starch acetate carrier agent (10: 1; 10: 2 and 10: 3), application of starch acetate as anthocyanin carrier agent of slurry, filtrate and purple sweet potato pulp, and powder anthocyanin stabilized test to temperature and pH. The composition raw based material contained moisture content (79.09 - 93.51%), carbohydrates (5.63 - 20.18%), starch (4.96 - 19.22%), and anthocyanin content of 7.74 - 11.58 mg/100 g. The ratio of slurry and starch 10:1 gave Chroma of 18.48 and oHueof  334.75. In stabilization stage, slurry form produced the best characteristics i.e.  anthocyanins content of 9.87 mg / 100 g, moisture content of 2.99%, Chroma of 15.92, oHue of 342.38, stable at a heating temperature of 80 oC and pH of 3 - 4 and also dissolved well at 80oC.  The result showed that acetilated starch binds purple sweet potato anthocyanins in slurry form more stable than those in filtrate and pulp.Keywords: anthocyanins, carrier agent, acetate starch